Pengaruh Brand Image dan Hedonistic Lifestyle terhadap Repurchase Intention Gen Z pada Starbucks Coffee - Yulia Natalia Elisabeth; Rezi Erdiansyah (Kiwari, 2023)
The development of an increasingly modern era has made people's lifestyles change, one of which is the lifestyle factor that leads to a hedonic lifestyle by seeking pleasure in the form of glamorous life such as hanging out with friends in coffee shops. The "coffee" trend has now become a hedonic lifestyle, especially among the Z generation, one of the coffee shops that is in great demand and has a good brand image in the minds of consumers is Starbucks. This study aims to determine whether there is an influence of Brand Image and Hedonistic Lifestyle on Repurchase Intention of Generation Z Starbucks consumers in Jakarta. This study uses correlational research with a quantitative approach with three variables, namely Brand Image (X1), Hedonistic Lifestyle (X2) and Repurchase Intention (Y). Data collection was obtained by distributing questionnaires online with a sample of 97 respondents who had consumed Starbucks products in Jakarta. The sampling technique uses Non-Probability Sampling with the Quota Sampling method. In this study, the analysis used was hypothesis testing and multiple linear regression with the help of the SPSS program. The results showed that Brand Image (X1) and Hedonistic Lifestyle (X2) had a positive and significant influence on Repurchase Intention (Y). Perkembangan zaman yang semakin modern membuat pola hidup masyarakat mengalami perubahan, salah satunya faktor gaya hidup yang mengacu terhadap gaya hidup hedonis dalam mencari kesenangan berupa kehidupan glamour seperti nongkrong bersama teman di coffee shop. Tren “ngopi” sekarang telah menjadi gaya hidup hedonis khususnya di kalangan generasi Z, salah satu coffee shop yang banyak diminati dan mempunyai brand image yang bagus di benak pelanggan ialah Starbucks. Pengkajian ini memiliki tujuan guna mengamati apakah adanya dampak brand image dan hedonistic lifestyle pada repurchase iintention pelanggan Starbucks generasi Z di Jakarta. Penelitian ini memakai pengkajian korelasional dengan pendekatan kuantitatif dalam tiga variabel, ialah Brand Image (X1), Hedonistic Lifestyle (X2) dan Repurchase Intention (Y). Pengumpulan data didapatkan dengan perluasan kuesioner dengan online dengan sampel sejumlah 97 responden yang telah mengonsumsi produk Starbucks di Jakarta. Teknik pengambilan sampel memakai Non-Probability Sampling dengan metode Quota Sampling. Pada pengkajian ini analisis yang dipakai memakai metode uji hipotesis dan uji regresi linier berganda pada bantuan program SPSS. Perolehan pengkajian menggambarkan jika Brand Image (X1) dan Hedonistic Lifestyle (X2) memiliki pengaruh positif dan signifikan terhadap Repurchase Intention (Y).